MENUMBUHKEMBANGKAN DAYA DAN DISPOSISI MATEMATIS SISWA SEKOLAH MENENGAH ATAS MELALUI MODEL PEMBELAJARAN INVESTIGASI - Mumun Syaban (Fakultas Keguruan dan Ilmu Pendidikan Universitas Langlangbuana, 2008)
his research is carried out to obtain the empirical evidence concerning capability of discovering to raise the mathematical power and disposition of senior high school students (SMA). The population in this research is Senior High School Students, with sampel is SMA students from high level, medium level and lower level in environment in Education Departement in Bandung. This research just using research of control group design especially post-test. To knowing ability of disposition and power mathematical student used by the instrument test. Analysis data in this research using one way and two way ANOVA.The research result obtained as follows:(1) The mathematical power and disposition of student study which is use the study model of investigation that better than the student which is use study conventionally. (2) The mathematical power and disposition of student which is using model study of investigation grouply better than that student study use the model study of investigation individually. (3) The mathematical power and disposition of student has the cognitive style field independent (FI) better than student has the cognitive style field dependent (FD). (4) There are interaction between study models with level to school in mathematical power. (5) There are interaction between study model with cognitive style. (6) There are interaction between study models with level to school in mathematical disposition. (7) There are no interaction between study models with cognitive style in mathematical disposition.Key Words: Mathematical power, mathematical disposition, Cognitive Styles, problem solving, communication, reasoning, connections, and group investigation.